2011
DOI: 10.1111/j.1740-8709.2011.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐upper arm circumference and weight‐for‐height to identify high‐risk malnourished under‐five children

Abstract: The World Health Organization and UNICEF define non-oedematous severe acute malnutrition (SAM) either by a mid-upper arm circumference (MUAC) less than 115 mm or by a weight-for-height z-score (WHZ) less than -3. The objective of this study was to assess whether there was any benefit to identify malnourished children with a high risk of death to combine these two diagnostic criteria. Data of a longitudinal study examining the relationship between anthropometry and mortality in rural Senegal and predating the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
154
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(164 citation statements)
references
References 7 publications
6
154
3
1
Order By: Relevance
“…However, the researchers in this study found that of the children with MAM, an acceptable MUAC measurement of > 12.5 cm was found in a large proportion of the sample, despite a WHZ lower than −2 SD having been recorded. This is in line with other international studies which, in conflict with the recommendations by Briend et al 17 and Goossens et al, 18 showed a poor correlation between WHZ and MUAC. 19,20 Thus, the sensitivity of MUAC in screening for MAM in South African populations with high levels of moderate and severe stunting should be questioned.…”
Section: Discussion and Recommendationscontrasting
confidence: 56%
See 1 more Smart Citation
“…However, the researchers in this study found that of the children with MAM, an acceptable MUAC measurement of > 12.5 cm was found in a large proportion of the sample, despite a WHZ lower than −2 SD having been recorded. This is in line with other international studies which, in conflict with the recommendations by Briend et al 17 and Goossens et al, 18 showed a poor correlation between WHZ and MUAC. 19,20 Thus, the sensitivity of MUAC in screening for MAM in South African populations with high levels of moderate and severe stunting should be questioned.…”
Section: Discussion and Recommendationscontrasting
confidence: 56%
“…However, it was demonstrated from recent data that nurses in the Western Cape had inadequate knowledge of the use of available nutritional status interpretation tools in the Road to Health booklets. 16 Simplifying nutritional screening by using MUAC alone to identify high-risk, malnourished children has been described by Briend et al 17 They found MUAC to be an acceptable screening tool in identifying children with severe acute malnutrition, with no benefit using WHZ in combination with MUAC or MUAC alone. MUAC has also been described by Goossens et al 18 to have many advantages over the use of WHZ.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The MUAC cut-off value having the same specificity for predicting death as a combination criterion of either MUAC < 11.5 cm or WHZ below −3 yielded a greater sensitivity. These findings concur with those of a recent secondary analysis of the risk of dying in a community-based data set in rural Senegal 16 and provide further evidence from a different setting that measuring both WHZ and MUAC does not result in improved identification of undernourished children at high risk of dying. Measurement of MUAC only could therefore replace the use of both MUAC and WHZ, depending on the MUAC cut-off value chosen.…”
Section: Discussionsupporting
confidence: 80%
“…Besides the simplicity of the use of MUAC and the ability to allow for high coverage, these reviews emphasize its superior effectiveness to identify children at high risk of death; they also indicate that there is no benefit in using WHZ < −3 in addition to MUAC < 115 mm as MUAC identifies high-risk children better than WHZ < −3 (12,13) . Moreover, the new global guidance by WHO indicating that MUAC ≥ 125 mm (without oedema for at least two weeks) should be used as discharge criterion for children admitted with MUAC < 115 mm can significantly simplify national protocols, the training and supervision of the staff involved in identifying and treating children, and the overall performance of programmes for the management of SAM (14) .…”
Section: Discussionmentioning
confidence: 99%